2016
DOI: 10.3855/jidc.5647
|View full text |Cite
|
Sign up to set email alerts
|

A duplex real-time PCR for the detection of Streptococcus pneumoniae and Neisseria meningitidis in cerebrospinal fluid

Abstract: Introduction: Acute bacterial meningitis is one of the most severe infectious diseases. Rapid, accurate, and inexpensive diagnosis of bacterial meningitis is crucial for patient management. This study describes a duplex real-time (RT) PCR assay for detection of Neisseria meningitidis and Streptococcus pneumoniae in the cerebrospinal fluid (CSF) for meningitis diagnosis using SYBR Green-based RT-PCR method coupled with melting curve analysis. Methodology: We used SYBR Green-based RT-PCR method coupled with melt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Furthermore, our assay offers high sensitive detection of N. meningitidis by using two gene targets. Cost estimation of our assays shows, like Diawara et al [28], that "in-house" method is more expensive than bacterial culture, which is estimated about 5 USD per test, but it is faster in obtaining a final result (less than 4 hours).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Furthermore, our assay offers high sensitive detection of N. meningitidis by using two gene targets. Cost estimation of our assays shows, like Diawara et al [28], that "in-house" method is more expensive than bacterial culture, which is estimated about 5 USD per test, but it is faster in obtaining a final result (less than 4 hours).…”
Section: Discussionmentioning
confidence: 70%
“…The developed method in our work was able to confirm all the positive cases revealed by the conventional methods (Group A and B) and to detect 7 other supplementary cases initially diagnosed negative by standard methods with high sensitivity performance. Previous studies such as Corless et al [10], Brouwer et al [6], Diawara et al [28] and Kahraman et al [29] have shown that rt-PCR was characterised by high performance sensitivity than conventional methods even by using Sybr Green or TaqMan technologies. The reported sensitivities varied between 72-92%, 61-100% and 88-94% for H. influenzae, S. pneumoniae and N. meningitidis respectively [6].…”
Section: Discussionmentioning
confidence: 99%
“…This is a complex task that traditionally requires multiple sample handling steps, and is often characterized by low selectivity and high rate of false negative or false positive signals due to cross-reactions with human DNA as well as not having enough DNA extracted from the samples. [4,5,[31][32][33] In the search of the shortest method for preparing DNA samples ready for PCR amplification, we attempted several strategies -a standard DNA purification kit, or treatment of bacteria-containing CSF samples with either lysozyme or NaOH prior PCR. As a control, we used untreated bacterial cells suspended in 2 μl CSF.…”
Section: Resultsmentioning
confidence: 99%
“…Even though quantitative polymerase chain reaction (qPCR) tests have received ever growing appreciation as a rapid tool for clinical diagnostics, they are not affordable by small clinics, especially in developing countries. [3][4][5] Moreover, qPCR requires expensive instrumentation and a specialized facilities often remote from point-of-care (POC) setting. Our long-term goal is to develop a fast and easy assay that can be performed at point-of-care settings with visual output.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, molecular methods have been developed to accurately diagnose S. pneumoniae in isolates and clinical samples. therapy (9). They are used for diagnosis of pneumococcal infections based on identical genes i.e.…”
Section: Introductionmentioning
confidence: 99%